SPELLING ERRORS AND MEANING-MAKING IN MASTER’S DISSERTATION AT A RURAL SOUTH AFRICAN UNIVERSITY - Matji, Ngwanamphaga Alettah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study was aimed at investigating the impact of spelling errors in meaning-making in the master’s dissertation written by university students. The researcher identified common spelling errors in dissertation writing within the department of language education in the School of Education at a rural university in South Africa. Six dissertations were selected from a sample of forty master’s students, using the random sampling technique. Data were collected using a qualitative method. A descriptive case study design was employed in this study, as a specific case was identified and analysed through qualitative, narrative explanation. Data were gathered from dissertation documents and classroom observations. It was found that the majority of the spelling problems result from pronunciation during dialogue. The findings suggest that the spelling errors were as a result of omission, addition, substitution of letters, incorrect word spacing, dialects, and punctuation. The study will greatly contribute to post-graduate studies by providing guidance on dissertations and ensuring that meaning is achieved.